Amphetamine-Like Analogues in Diabetes: Speeding towards Ketogenesis - Natalia M. Branis; Steven D. Wittlin (Case Reports in Endocrinology)
Obesity is common in patients with type 1 and type 2 diabetes. Amphetamine-like analogues comprise the most popular class of weight loss medications. We present a case of a 34-year-old African American female with a history of type 1 diabetes, dyslipidemia, and obesity who developed diabetic ketoacidosis (DKA) after starting Diethylpropion for the purpose of weight loss. Shortly after starting Diethylpropion, she developed nausea, vomiting, and periumbilical pain. Blood work revealed glucose of 718 mg/dL, pH 7.32 (7.35–7.45), bicarbonate 16 mmol/L (22–29 mmol/L), and anion gap 19 mmol/L (8–16 mmol/L). Urine analysis demonstrated large amount of ketones. She was hospitalized and successfully treated for DKA. Diethylpropion was discontinued. Amphetamine-like analogues administration leads to norepinephrine release from the lateral hypothalamus which results in the appetite suppression. Peripheral norepinephrine concentration rises as well. Norepinephrine stimulates adipocyte lipolysis and thereby increases nonesterified fatty acids (NEFA) availability. It promotes β-oxidation of NEFA to ketone bodies while decreasing metabolic clearance rate of ketones. In the setting of acute insulin deficiency these effects are augmented. Females are more sensitive to norepinephrine effects compared to males. In conclusion, amphetamine-like analogues lead to a release of norepinephrine which can result in a clinically significant ketosis, especially in the setting of insulin deficiency.